Template Removal via Boudouard Equilibrium Allows for Synthesis of Mesostructured Molybdenum Compounds. (3rd January 2017) - Schieder, Martin; Bojer, Carina; vom Stein, Julia; Koch, Sebastian; Martin, Thomas; Schmalz, Holger; Breu, Josef; Lunkenbein, Thomas
Abstract: Oxidative thermal removal of the polymeric templates is not trivial for molybdenum oxides and hampers mesostructuring of this material. At ambient oxygen fugacity, Mo VI is the thermodynamically stable oxidation state and sublimation of MoO3 leads to a quick loss of the mesostructure through Oswald ripening. Taking advantage of the Boudouard equilibrium allows to fix the oxygen fugacity at a level where non‐volatile MoO2− x is stable while carbonaceous material may be oxidized by CO2 . Mesostructured MoO2− x can be chemically converted into MoO3 or MoN under retention of the mesostructure.